OLIY TAʼLIM MUASSASALARINING INNOVATSION TAʼLIM LOYIHALARI ASOSIDA RAQOBATBARDOSHLIGINI OSHIRISH (Marketing Jurnali, 2025)
This article analyzes the enhancement of higher education institutionsʼ competitiveness through the implementation of innovative educational projects . A strategic management approach based on a three -block model ( target , functional , and operational ) is proposed . The study explores opportunities for preparing universities for global competition via digital transformation , financial autonomy , marketing, and public -private partnerships . Recommendations are provided for building a sustainable innovation ecosystem through the integration of education , science , and industry .
Keywords: innovatsion taʼlim; raqobatbardoshlik; strategik boshqaruv; raqamli transformatsiya; oliy taʼlim; universitet boshqaruvi; taʼlim ekotizimi; davlat - xususiy sheriklik